Product Market Competition, Incentives and Fraudulent Behavior - Rainer Andergassen (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2008)
The present paper studies incentive provision in a model where a manager can affect the firm's stock price by exerting unobservable effort and through costly, deceptive signalling and investigates the role product market competition plays in shaping shareholders' trade-off between inducing effort and fraud.
Keywords: 330